A Sociological Assessment on the Examples of Veiling as an Indicator of Gender at the Ancient Anatolian Societies - Şahin, Mehmet Cem; Demirdağ, Muhammet Fatih; Aydemir, Salih (Journal of History Culture and Art Research, 2018)
Gender is, as distinct from sexuality, identified by society and culture that individual was born in. Just as people congenitally have some roles depending on their biological differences, they also have some other roles given by society and behaviour patterns expected to exhibit. It has diversely appeared in all periods of time and societies that to express of such roles, statuses and behaviour patterns. Throughout history, one of the most significant demonstrations of woman’s gender was to be veiling. Veiling is a socio-cultural practice that can be traced back to the earliest times in human history. In ancient societies, people, especially women, have differentiated each other through various forms of covering, which symbolize the status and roles they are placed in society. In the historical process, due to various social, economic, religious, cultural and political transformations experienced, the differentiation that took place in the social status of women led to some changes in the practices of covering. In archaeological finds belonging to ancient Anatolian societies, such as in the tombstones, women are sometimes depicted as a noble wife, sometimes a temple official, sometimes as a servant. In fact, some Anatolian societies have portrayed their master goddesses in an implicit way, including their heads. It is known that the depictions of the mother goddess cult (Magna Mater, Kybele, Artemis, Hera and Mary cults) are depicted as garnished in Old Anatolian societies in the later stages due to the interaction of eastern and western civilizations. It is known that the depictions of Mother goddess cult without clothes are depicted as garmented in Old Anatolian societies due to the interaction of eastern and western civilizations in later stages. In this article, some sociological determinations and evaluations are made about the practice of veiling in the light of some archaeological findings related with ancient Anatolian civilizations.